Synergistic Interactions Among Iron and Cobalt Atoms Within Bimetallic Molybdate@Carbon Paper Composite Create Bifunctional Nanoflower Electrocatalyst, Enhancing Efficiency for Overall Water Splitting in Alkaline Environment - Ting Cheng; Fei Wu; Chen Chen; Xiao Zhang; Mengyi Zhang; Liwei Cui; Youzhi Dai; Baoxuan Hou; Yuan Tian; Jiarui Zhu (Molecules)
Electrocatalytic water splitting is a promising approach for obtaining clean hydrogen energy. In this work, novel molybdate@carbon paper composite electrocatalysts (CoxFe10-xMoO@CP), displaying outstanding electrocatalytic capabilities, were deriving from anchoring cobalt/iron molybdate materials onto the surface of carbon paper fibers. By adjusting the cobalt-to-iron ratio, the composite (Co5Fe5MoO@CP), with the optimal molar proportion (Co/Fe = 5/5), exhibited a distinctive nanoflower morphology (50–100 nm), which provided a significant number of active sites for electrocatalytic reactions, and showed the strongest electrocatalytic potency for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Specifically, the overpotentials for HER and OER were 123.6 and 245 mV at 10 mA·cm−2, with a Tafel slope of 78.3 and 92.2 mV·dec−1, respectively. The hydrogen and oxygen evolution reactions remained favorable and stable over 35 days and 2 weeks of cyclic voltammetry cycles. In a two-electrode system, efficient overall water splitting was achieved at a cell voltage of 1.60 V. Under high alkaline concentration and temperature conditions, the Co5Fe5MoO@CP composite still maintained excellent HER and OER catalytic activity and stability, indicating its satisfactory potential for industrial applications. Density functional theory (DFT) analysis revealed that the promoted hydrogen evolution capability derived from the synergistic catalytic effect of iron and cobalt atoms within the molecule, while cobalt atoms functioned as the catalytic core for the oxygen evolution process. This work provides a novel strategy towards high-efficiency electrocatalysts to significantly accelerate the overall water splitting.